The Influence of Time Management, Self-Actualization, and Work Family Conflict on the Performance of Sampang District Office Employee, Cilacap Regency - Khaerunisa, Natanila Putri; Siti Zulaikha Wulandari; Retno Kurniasih (Awatara Publisher, 2024)
In general, this research aims to analyze the influence of Time Management, Self-Actualization, and Work Family Conflict on Employee Performance. The respondents for this research were all employees of the Sampang District Office, Cilacap Regency. Based on the results of research and data analysis using multiple regression, it can be concluded that: (1) Time Management has a significant effect on Employee Performance. (2) Self-actualization does not have a significant effect on Employee Performance. (3) Work Family Conflict has no significant effect on Employee Performance. The implication of this research is that to improve employee performance, agencies are expected to encourage employees to manage their time well and determine priority scales so that they can complete tasks more effectively and efficiently. Apart from that, agencies are also expected to always supervise and encourage their employees to continue to improve their abilities at work, this can be done by carrying out training activities for their employees. This is intended so that employees continue to maintain their efforts to always improve their abilities so that they can provide the best for their work.